CT-3D MERGE fusion imaging improves image quality compared with CT and 3D MERGE in patients with lumbar disc herniation - Li, Hongyi; Liu, Hailong; Xiao, Mengqiang; Du, Xiaodan; Zhang, Meng; Ye, Jingzhi; Lei, Ming; Chen, Jun; Chen, Jie (Frontiers in Neurology, 2024)
BackgroundCT-routine MRI fusion imaging has recently become available to evaluate spinal anatomy before surgery. Due to the 3-5 mm slice thickness and non-isotropic of routine MRI sequence, the CT-routine MRI fusion imaging is not good. The MRI multiple recalled gradient echo (MERGE) sequence is potentially useful in diagnosis of lumbar degeneration disease due to the better nerve roots visualization, 1 mm slice thickness and its isotropy.PurposeThe present study aimed to evaluate the image quality of CT-3D MERGE fusion images compared with CT and 3D MERGE images in patients with lumbar disc herniation.MethodsFifty-nine patients with lumbar disc herniation who underwent both lumbar CT and MRI including 3D-MERGE and routine lumbar MRI sequences were evaluated. All CT, 3D MERGE and CT-3D MERGE fusion images were separately assessed by two radiologists using five-point Likert scoring method based on five aspects: display of bony structure, intervertebral discs, nerve roots, overall anatomical details and image artifacts. Furthermore, two observers documented the sacral slope (SS), L4/5 intervertebral space heights (ISH), width and height of L4/5 intervertebral foramen (FW and FH) on CT and CT-MERGE fusion images.ResultsThere was insufficient evidence to show a difference in bony structure score between CT and CT-3D MERGE fusion images (p = 0.22), but it was significantly higher than that of MERGE (p < 0.001). The scores of intervertebral discs and nerve roots between MERGE and fusion images were not statistically different (p = 0.19 and 0.88), which were higher than CT (all p < 0.001). The overall anatomical detail score of fusion imaging was higher than CT and MERGE (p < 0.001). No significant difference of image artifacts score was found among CT, MERGE and fusion images (p = 0.47). There was no significant difference in SS, ISH, FW, FH values between CT and fusion images (all p > 0.05).ConclusionCT-3D MERGE fusion images exhibit superior image quality to both CT and 3D MERGE for the simultaneous observation of bony structures, intervertebral discs, and nerve roots.